A descriptive study of professional staff, and their careers, in Australian and UK universities. (2nd January 2018) - Gander, Michelle
ABSTRACT: Professional staff total approximately 23% of staff in universities in the UK, which in 2014/15 was the equivalent of 95, 870 individuals (hesa.ac.uk). With their increasing span of responsibility, it is surprising that there has been little research into the careers of these staff. This study, part of a larger careers study, highlights some key attitudes to, and needs from, their careers. Via a multi-method instrument, of which only descriptive statistics are presented here, it is shown that professional staff are motivated by an integrated set of needs attributed to traditional, boundaryless and protean career theory. It is also shown that professional staff overall are satisfied in their roles, but there is a mismatch between the desire for a career and promotion opportunities, and those forthcoming from their organisations.